Quantifying the amount of restraining due to friction in the different areas of drawing tools: A numerical analysis - Saenz-de-Argandona Eneko; Zabala Alaitz; Guinea Ainhoa; Cañizares Daniel; Mendiguren Joseba (MATEC Web of Conferences)
It is nowadays well known that depending on the tool surface topography, sheet surface topography, lubricant nature and amount, and process variables a wide range of coefficient of friction (COF) values coexist in the very same drawing operation. Furthermore, and as shown in a previous publication of the research group, the tool finishing is not homogeneous and different roughness values are observed in industrial tooling. So the question that arrives in this situation is what areas of the tool have a greater impact in the material restraining and therefore more efforts should be applied when polishing them. The present work numerically analyses three industrial drawing operations of big automotive components. A classification of the different areas of the tool is carried out and friction is activated and deactivated in different numerical simulations. A comparison in terms of draw in, material formability (based on FLD), major strain and thinning is carried out. As a result, a classification of the tool areas that most impact have in the restraining of the material is carried out.